Control of banana Xanthomonas wilt disease using genetic engineering - Tripathi, L.; Tripathi, J.N.; Tushemereirwe, Wilberforce K. (International Society for Horticultural Science, 2010)
The banana Xanthomonas wilt (BXW) disease, caused by the bacteriumXanthomonas campestris pv. musacearum (XCM), endangers the livelihoods ofmillions of farmers in the Great Lakes region of East and Central Africa. Thedisease was first identified in Uganda in 2001 and has since then also been reportedin Eastern Democratic Republic of Congo, Rwanda, Kenya and Tanzania. Thepathogen kills plants quickly and spreads rapidly over a large area making thedisease one of the most dreaded in banana (Musa spp.). The development of diseaseresistant banana cultivars remains a high priority, since farmers are reluctant toemploy labor-intensive disease control measures. Prospects of developing cultivarswith resistance to BXW through conventional breeding are limited, as no source ofgermplasm exhibiting resistance against XCM has been identified. Transgenictechnologies for banana may provide a timely and cost-effective alternative solutionto the BXW pandemic. The ferredoxin-like amphipathic protein (pflp) andhypersensitive response assisting protein (hrap), isolated from sweet pepper(Capsicum annuum) are novel proteins that can intensify the harpinPSS-mediatedhypersensitive response. The International Institute of Tropical Agriculture (IITA)has negotiated royalty-free license from Academia Sinica, Taiwan, patent holder,through the African Agricultural Technology Foundation (AATF) for access to thetechnology for bacterial wilt resistance. The partners, IITA, the NationalAgriculture Research Organization (NARO) in Uganda and AATF, have signed atripartite agreement for development of BXW-resistant transgenic bananas.Hundreds of transgenic lines of banana cultivars have been generated, which arescreened for disease resistance under laboratory conditions. Most promising lineswill be evaluated for efficacy against XCM in fields.